Facility-led community based approach in Mamfe health district, Cameroon: a differentiated service delivery option in complex humanitarian settings - Enongene Julius Mekolle; Kate Ivo Keumami; Omeichu Agwenam Amadeus; Agbor Nyenty Agbornkwai; Ismaila Esa; Aseh Christian Chuyum (BMC, 2023)
Abstract Background The government of Cameroon's 2017 operational guidelines for the implementation of the "test and treat" strategy expressly incorporates and prescribes the differentiated service delivery (DSD) model with testing and treatment services being decentralized and task shifted at community level. However, express guidance on DSD approach in conflict situations, characterized by pressure on existing health systems remains a limitation. The outbreak of COVID-19 further confounded humanitarian responses for fear of spread. Facility-led community-based approach (FLCBA) was employed as a model of care in addressing DSD for HIV in conflict-affected settings within the COVID-19 context. Methods A retrospective quantitative cross-sectional study was conducted in Mamfe District Hospital. Descriptive statistics was used to evaluate the implementation of FLCBA as a DSD model from April 2021 to June 2022 along the clinical cascades. Data were collected using a chart abstraction template from the respective registers. Analyses were done using Microsoft excel 2010. Results In 15 months, a total number of 4707 (2142 males, 2565 females) people were screened for HIV and 3795 (1661 males, 2134 females) eligible individuals were tested. Out of the 11 targeted health areas, 208 (5.5%) new positive cases were identified, all (100%) of whom were linked to care and treatment. During this period, 61% (34/55) targeted missing clients were tracked through this means among which 31 were defaulters and 3 LTFU. Of the 196 target clients for FLCBA, eligible for viral load sample collection, 142 (72%) samples were collected. Conclusions The FLCBA as an integral primary health care delivery package is an efficient and effective variant of DSD for conflict settings; however it requires bravery of health care providers.